Studi Eksperimental Titik Nyala dan Viskositas Biodiesel Diproduksi dari Minyak Goreng Bekas - Hussein, Muhammad; Idris, Muhammad (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2024)
Biodiesel is a potential alternative to replace diesel because its raw materials are renewable and environmentally friendly. One of the raw materials used is waste cooking oil. The high content of free fatty acids in waste cooking oil requires pretreatment in the form of esterification before the transesterification process. This study aims to determine the effect of reaction time variations (60, 70, 80, 90, and 100 minutes) at a temperature of 60°C and a stirring speed of 1050 rpm on biodiesel's flash point and viscosity. The biodiesel production process was carried out in two stages: esterification and transesterification. The catalyst concentration was methanol at a 1:2 ratio and NaOH at 0.5% of the waste cooking oil. After transesterification, the mixture was allowed to settle for 20 minutes. The produced biodiesel was washed with distilled water at 50°C and evaporated at 90-100°C. The flash point test results for the reaction time variations showed the following values: 60 minutes (108.5), 70 minutes (182.5), 80 minutes (182.5), 90 minutes (148.5), and 100 minutes (184.5). The results indicated that the cetane number obtained did not meet the biodiesel quality standards and was not yet suitable for use according to the Ministry of Energy and Mineral Resources (ESDM) regulations.